Educational Leadership Capacity Building Program in Decision Making through CIVI Leadership Model: Program Peningkatan Kapasitas Kepemimpinan Pendidikan dalam Pengambilan Keputusan melalui Model Kepemimpinan CIVI. - Diding Nurdin; Octavira, Ira Nadya; Johar Permana; Eka Prihatin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The condition of education in Indonesia after the pandemic experienced is getting learning loss or setbacks. The results of the INOVASI study found that early grade students in Indonesia experienced an indication of loss of learning outcomes equivalent to 0.47 standard deviation/sd (or 6 months of learning). This figure is much higher than in the United States (0.14) or China (0. 22). The independent curriculum is the main alternative offered by the government to catch up through driving schools which are pilot projects in implementing this independent curriculum. The implementation of good and appropriate education in schools certainly cannot be separated from the performance of the school principal. This is also a challenge for the government to be able to provide intervention to school principals so that they can become good captains in implementing the independent curriculum. This activity was carried out using the socialization method of the driving school leadership model which was designed based on field studies and relevant literature reviews. Based on the results of the research conducted, there was an increase in understanding, knowledge and skills of private school principals in Sukabumi City in terms of decision making. This is also proven by increasing the education report card scores of educational units within one year. With this activity, it is hoped that school principals will be able to further explore their abilities through Educational Leadership Capacity Building Program